Determination of normative data on non invasive electrocochleography test in Malaysian adults - Musa, Zalilah (2015)
Objective The study was conducted with the aim to obtain normative data of Electrocochleography (EcochG) among Malaysian adults. It is also done to compare EcochG outcomes amplitude of summating potential (SP), action potential (AP) and SP/AP ratio between two different placements of EcochG electrode at the upper part of tympanic membrane and lower part of tympanic membrane and the difference between male and female. Methodology This is a cross sectional study conducted at audiology clinic HUSM starting from November 2011 until June 2012. 30 adults who consist of HUSM staffs aged 18 to 50 years old were chosen using simple random sampling method. Subjects were confirmed to have no pathological ear by otoscopy and have normal hearing level on pure tone audiometry (PTA).Tympanic electrode by Biologics was used. The gel is applied at its tip prior to insertion. With the help of head light,the electrode is introduced firstly at upper part of tympanic membrane until subject feels that it touches the membrane with the placement of insert earphone below the electrode. Broadband alternating clicks 95 dBHL at 7.1/s is given to the patient and result recorded. After recording of upper placement finished, the electrode is then placed at lower part of tympanic membrane with the insert earphone above it. Same stimulus given and result recorded. Results EcochG data between males and females are combined because there was no significant difference between them ( p > 0.05 ). The mean SP/AP ratio is 0.31 for upper TM placement and 0.30 for lower TM placement. The mean for AP are 0.72uVand 0.66uV for upper TM and lower TM respectively where as mean SP is 0.23uV for upper TM and 0.20uV for lower TM. Conclusion The normative data for EcochG parameters were obtained. The mean for AP, SP and SP/AP ratios are 0.69u ,0.21uV and 0.31 respectively. There was no difference in EcochG reading of right and left ear between two different placements of tymptrode with p value of 0.49 (p > 0.05). There was also no difference in EcochG parameters between male and female with p value of 0.96 ( p > 0.05 ).